2015
DOI: 10.1149/2.0141512jes
|View full text |Cite
|
Sign up to set email alerts
|

A Fundamental Study of Boron Deposition and Poisoning of La0.8Sr0.2MnO3Cathode of Solid Oxide Fuel Cells under Accelerated Conditions

Abstract: Borosilicate glass and glass-ceramics are the most common sealant materials for planar solid oxide fuel cells (SOFCs). This study focuses on the fundamentals of deposition and poisoning of volatile boron species from the borosilicate glass on the electrocatalytic activity and microstructure of La 0.8 Sr 0.2 MnO 3 (LSM) cathodes under accelerated SOFC operation conditions, using EIS, SEM, FIB-SEM, HRTEM, NanoSIMS, XPS and ICP-OES. The presence of boron species poisons and deteriorates the electrochemical activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Polarization can significantly affect the distribution of deposited boron. Chen et al [229,230] conducted the in situ electrochemical study of boron poisoning in LSM electrodes under cathodic and anodic polarization at 800 °C in which borosilicate glass pellets were placed on top of an LSM electrode as a boron source without direct contact by using a Pt mesh buffer layer. Here, it was found that boron deposition occurred randomly on the LSM electrode surface under open circuit conditions but was driven to the electrode/electrolyte interface region under cathodic polarization, resulted in the formation of LaBO 3 and Mn 2 O 3 and the disintegration of the LSM perovskite structure (Fig.…”
Section: Boronmentioning
confidence: 99%
“…Polarization can significantly affect the distribution of deposited boron. Chen et al [229,230] conducted the in situ electrochemical study of boron poisoning in LSM electrodes under cathodic and anodic polarization at 800 °C in which borosilicate glass pellets were placed on top of an LSM electrode as a boron source without direct contact by using a Pt mesh buffer layer. Here, it was found that boron deposition occurred randomly on the LSM electrode surface under open circuit conditions but was driven to the electrode/electrolyte interface region under cathodic polarization, resulted in the formation of LaBO 3 and Mn 2 O 3 and the disintegration of the LSM perovskite structure (Fig.…”
Section: Boronmentioning
confidence: 99%
“…112 In the case of the oxygen reduction reaction on LSM under the cathodic polarization conditions, similar boron deposition phenomenon was also observed at the electrode/electrolyte interface region. 113 On the other hand, under the open circuit conditions boron deposition is random without preferential distribution. 113 In the reactions, La 0.8 Sr 0.2 MnO 3,interface↑ stands for the energetic and active state of LSM at the interface under the anodic polarization.…”
Section: Degradation Of Electrolytementioning
confidence: 99%
“…113 On the other hand, under the open circuit conditions boron deposition is random without preferential distribution. 113 In the reactions, La 0.8 Sr 0.2 MnO 3,interface↑ stands for the energetic and active state of LSM at the interface under the anodic polarization. It would be expected the similar deposition and poisoning effect of boron species on the electrocatalytic activity of LSCF oxygen electrodes.…”
Section: Degradation Of Electrolytementioning
confidence: 99%